Prediction of effort required to design software for smart city applications. (January 2021) - Rai, P; Kumar, S; Verma, D K
Abstract: In present era smart cities are essential for further development. The fast growth in the urban population is a serious concern for city administration. It leads to various challenges while handling problems of resource crunch and managing them. Developments that relate to smart cities are helping the administration address these problems. Its initial effort prediction and its scalability are the main features for the completion of a successful smart-city project. The initiative depends on many factors that are inter-related. It is not possible to change or optimise certain kinds of aspects separately. The last-minute change in the schedule raises the project budget and time. In the early phases of the project, a realistic and concrete project plan needs a fair estimate of effort. This projected effort helps to monitor and handle the activities of application creation by the developer. Unfair allocation of efforts and resources between development activities, including software projects, contributes to the failure of smart city projects, too. Therefore, for smart city ventures, the secret to success is an accurate estimation of implementation activities at the earliest. Numerous approaches are available for effort prediction of software as well as hardware projects used to develop the smart city projects. Hence, the gap in the different methods available creates thrust areas for researchers to investigate and propose an effort prediction model for smart city-based projects. In this paper, a model has been formulated that takes into consideration a set of critical factors for a given IoT based application used to develop smart city in the subject, and it further provides estimation for the effort.